The Effect of Splint Material Rigidity in Implant Impression Techniques - Del'Acqua, Marcelo Antonialli; Chavez, Alejandro Munoz [UNESP]; Castanharo, Sabrina Maria [UNESP]; Compagnoni, Marco Antonio [UNESP]; Mollo Junior, Francisco de Assis [UNESP] (Quintessence Publishing Co Inc, 2010)
Purpose This in vitro study compared the dimensional accuracy of two impression techniques Duralay splinted impression copings (D) and metal splinted impression copings (M) for implant supported pros theses Materials and Methods A master cast with four parallel implant abutment analogs and a passive framework were fabricated Vinyl polysiloxane impression material was used for all impressions with a metal stock tray Two groups (D and M) were tested (n = 5) The measurement method employed was just one titanium screw tightened to the framework Each group s measurements were analyzed using software that received the images of a video camera coupled to a stereomicroscope at X100 magnification The results were analyzed statistically (t test) Results The mean values of abutment/framework interface gaps were master cast = 32 mu m (SD 2), group D = 165 mu m (SD 60), and group M = 69 mu m (SD 36) There was a statistically significant difference between the D and M groups (P <= 001) Conclusion Under the limitations of this study, it could be suggested that a more accurate working cast can be fabricated using metal splinted impression copings INT J ORAL MAXILLOFAC IMPLANTS 2010 25 1153-1158
Keywords: dental implant; implant impression technique; splinting material